Teachers’ and Students’ Perspectives on Communicative Language Teaching (CLT) in EFL: A Systematic Review - Bedah, Bedah; Tarihoran, Naf’an; Heryatun, Yayu (International Journal of Science Education and Cultural Studies, 2026)
This study examines the perspectives of teachers and students on the Communicative Language Teaching (CLT) method in English as a Foreign Language (EFL) by employing a systematic approach guided by the PRISMA framework. Of the total 225 journals found through the Mendeley, Taylor&Francis, and ScienceDirect databases (2020-2024), as many as 21 relevant articles were analyzed in depth. The research methods include, qualitative evaluation, using library research. The result of the study showed that CLT has great potential in improving students' communication skills through activities such as group discussions and real-life situations. Students show a positive attitude towards CLT because the activities are relevant to their communication needs. However, challenges such as time constraints, supporting materials, and teacher training hinder its implementation. Many teachers continue to use traditional methods due to limited training and institutional support, even though they recognize the benefits of CLT. The study recommends intensive training for teachers, curriculum reform, and the use of digital tools to support CLT learning. Adaptation of this method to the cultural and social needs of students is also needed to maximize learning outcomes. These findings provide important insights for the development of education policies that support the effective implementation of CLT.